An intersectionality perspective on tuberculosis: social determinants affecting tuberculosis mortality rate in Ecuador - Rodríguez-Pazmiño, Ángel Sebastián; Paredes-Núñez, Darwin; Ramos-Sarmiento, Daniel; Lalangui-Vivanco, Karina; Orlando, Solon Alberto; Narvaez, Alexandra; Franco-Sotomayor, Greta; Garcia-Bereguiain, Miguel Angel (Frontiers in Public Health, 2025)
IntroductionThe Intersectionality approach to studying tuberculosis (TB) is a complex one. While historical data and indicators consistently suggest a positive correlation between social determinants, such as poverty, and TB mortality, the strength of this association varies across different regions and countries. Overcrowding and population density are also recognized as risk factors for TB transmission.MethodsIn this study, we conducted a descriptive and observational statistical analysis of TB mortality in Ecuador using the most recent public data from 2010. We examined the association between TB mortality and poverty, as well as territorial distribution, population density, and overcrowding.ResultsOur univariate analysis results indicate that the rural parishes or canton capitals in the first quintile of poverty (Q1) had the highest average mortality rates (14.23 per 100,000 inhabitants). Furthermore, the average TB mortality ratio was substantially higher in rural areas compared to urban ones (12.72 vs. 7.5 per 100,000 inhabitants). Interestingly, zones with the highest population density had a significantly lower average TB mortality ratio than those with the lowest density (4.82 vs. 15.19 per 100,000 inhabitants). Likewise, overcrowding analysis reveals a significant difference between the group with the highest level (O1) vs. the lowest one (O5; 14.3 vs. 6.8 per 100,000 inhabitants). On the other hand, a multivariate linear regression model agrees that three of the four independent variables evaluated had statistically significant associations with tuberculosis mortality rate. The percentage of poverty, living in a rural area, and population density were significant predictors of higher mortality. In contrast, the level of overcrowding, as determined by multivariate analysis, did not show a significant association when the other independent variables were taken into account.DiscussionThese findings reinforce the strong link between TB mortality and poverty, rurality, a discreet relationship with overcrowding, and an inverse relationship with population density in the Ecuadorian context, highlighting the need for targeted public health interventions in rural underserved communities. Future research should explore how changes in socioeconomic conditions and healthcare access have influenced TB incidence.